THUNDERSTORMS-RISK FACTORS IN AVIATION. CASE STUDY: AREA OF RESPONSABILITY OF THE BUCHAREST-OTOPENI AERODROME ON 30.06.2009 - C. L. ŞCHIOPU (Riscuri şi Catastrofe, 2015)
Thunderstorms are always dangerous weather phenomena for flight safety and, irrespective of their nature, they have a negative impact on all aviation activities. Thunderstorm clouds can generate severe and rapid changes of various meteorological elements (visibility, cloudiness and cloud lower base, wind), sometimes to such a great extent that landing may become impossible. Thunderstorms are serious weather hazards in aviation and may produce great damage and even casualties. One such unfortunate aviation event took place in the vicinity of the Bucharest-Otopeni Aerodrome, on 30.06.2009, when a military aircraft, which was operating a training flight in the responsibility area of the Bucharest - Otopeni military aerodrome, was struck by lightning at local hour 18:20. The present study actually makes an inventory of the extremely hazardous flying conditions, by thoroughly analyzing the relevant weather reports and data, as well as visual and synoptic messages from that very day. All these materials showed that the airdrome of destination was under the influence of an anti-cyclonic ridge, which accounted for the very poor meteorological conditions. On such severe weather, although the crew members tried to avoid the Cumulonimbus clouds in which a severe thunderstorm was developing, the flight was put in danger since the aircraft was struck by lightning, which simply blurred out the radar system and, therefore, landmarks orientation became almost impossible, thus creating false perceptions to the pilots trying hard to stabilize the plane.